2019
DOI: 10.20518/tjph.381667
|View full text |Cite
|
Sign up to set email alerts
|

General disaster preparedness beliefs and related sociodemographic characteristics: The example of Yalova University, Turkey

Abstract: Aim: This study aimed to identify sociodemographic and disaster related factors associated with General Disaster Preparedness Belief using the Health Belief Model as a theoretical framework. Methods: The survey study was conducted in Yalova, Turkey between April and July, 2014. A prevalidated General Disaster Preparedness Belief scale instrument based on the Health Belief Model was administered to a study group of 286 academic and administrative staff. The General Disaster Preparedness Belief score was compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Bu bölümde araştırmaya katılan öğrencilerin sosyodemografik özellikleri, acil durum/afet ile ilgili faktörlerin genel afete hazırlık inancı üzerine etkisi tartışılmıştır. (Inal et al, 2019). Genel afete hazırlık inanç ölçekleri toplam puan ortamlarının benzer ve ortalamanın üzerinde olduğunu göstermektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu bölümde araştırmaya katılan öğrencilerin sosyodemografik özellikleri, acil durum/afet ile ilgili faktörlerin genel afete hazırlık inancı üzerine etkisi tartışılmıştır. (Inal et al, 2019). Genel afete hazırlık inanç ölçekleri toplam puan ortamlarının benzer ve ortalamanın üzerinde olduğunu göstermektedir.…”
Section: Discussionunclassified
“…Bu araştırmaya katılan öğrencilerin genel afete hazırlık inanç ölçeği ve alt boyut puan ortalamaları incelendiğinde; öz yeterlilik alt boyutu puan ortalaması 30.55±4.57, algılanan duyarlılık alt boyut puan ortalaması 21.51±2.90, algılanan engeller alt boyut puan ortalaması 19.92±4.07 ve genel afete hazırlık inanç ölçeği toplam puan ortalaması 111.57±12.36 olarak tespit edilmiştir Inal et al (2019). tarafından Yalova Üniversitesi akademik ve idari personeline yapılan bir araştırmada benzer şekilde öz yeterlilik alt boyut puan ortalaması 24.69±6.35, algılanan duyarlılık alt boyutu puan ortalaması 26.57±4.04, algılanan engeller alt boyut puan ortalaması 18.58±4.07 ve genel afete hazırlık inanç ölçeği toplam puan ortalaması 107.03±14.02 olarak tespit edilmiştir…”
unclassified
“…Furthermore, it can be observed that employed individuals are more familiar with safety procedures and express greater readiness for evacuation. In a study conducted at Yalova University in Turkey [42], the relationship between general beliefs about disaster preparedness and various socio-demographic characteristics was examined, with a particular focus on the different impacts of employment. The overall score of general beliefs in disaster preparedness was statistically significantly associated with higher monthly income, higher employment status, previous experience with any disaster, and attendance of any disaster-related training.…”
Section: Employment Statusmentioning
confidence: 99%
“…Furthermore, it can be observed that employed individuals are more familiar with safety procedures and express greater readiness for evacuation. In a study conducted at Yalova University in Turkey (Inal, Altıntaş, & Doğan, 2019), the relationship between general beliefs about disaster preparedness and various socio-demographic characteristics was examined, with a particular focus on the different impacts of employment. The overall score of general beliefs in disaster preparedness was statistically significantly associated with higher monthly income, higher employment status, previous experience with any disaster, and attendance of any disaster-related training.…”
Section: Employment Statusmentioning
confidence: 99%